A gestão da propriedade intelectual nos Institutos Federais : ações para construção de uma cultura de propriedade intelectual no âmbito do Instituto Federal de Educação, Ciência e Tecnologia de Pernambuco - Loureiro, Rodrigo Nogueira Albert (2016)
The Professional and Technological Education is a centuries-old modality teaching in Brazil, dated 1909 with the signing of decree 7566, by President Nilo Peçanha, through by historical process of evolution with the conversion to Federal Technical Schools (FTS) and Federal Centers of Technological Education (FCTE). Since 2008 with publication of Law 11892 the Brazilian Professional and Technological Education gets new status by creation of Federal Professional Education Network (FPEN) and Federal Institutes of Professional, Scientific and Technological Education (FIs). The FIs provides education in diverse levels of teaching, offering high, middle and professional education, emphasizing professional and technological education (BRAZIL 2008). Institutes also encourage applied research at development of technical and technological solutions; entrepreneurship; and scientific and technological development directed to innovation processes. In 2004, concerning innovation, was publicated the Law 10973, known as the Innovation Act, which determines through Art.16 that all Scientific and Technological Institutions (STI) should have an Innovation Center (NIT) which to manage the institution's innovation policy. Besides, the Innovation Law stipulates that ICT's, through the NIT and annually to inform the Ministry of Science, Technology and Innovation by the "Form for Information on Intellectual Property Policy Scientific and Technological Institutions of Brazil" (FORMICT), the applied and granted protection, licensing agreements and transfer performed, in addition to questions about the level of implementation of the NIT. Now, all thirty-eight FIs have a NIT established, however, this was not a determining factor in the expansion of protection of intellectual property (IP) from some of these Institutes. FORMICT 2014 data showed that the thirty-seven FIs who filled out that form, less than half reported having done some kind of protection for their inventions. In the context of RFEPCT, the Federal Institute of Education, Science and Pernambuco Technology (FIEP) implemented your NIT in 2010 and in 2013 held its first IP protection from reformulation of actions taken by the referred core. Currently, the FIEP has thirteen patents filed at the National Institute of Industrial Property (NIIP), and three records of software and a brand. In this context, this research came from the motivation and interest in understanding the relationship between innovation management actions that resulted in a higher IP protection under the FIEP. As well as goals to achieve this purpose, we have: to present an overview of the implementation of NITs that reflects the situation of IP protection of IFs; map the actions of management of the NIT IFPE innovation; as well as to assess these actions on the user's perspective.